Successful professional reviews for civil engineers - Steels, H. Macdonald (ICE, 2011)
Providing a comprehensive guide to the constituent parts of the ICE Professional Review process, the author clarifies the attributes that lead to success. Working logically through the review process, the chapters ensure that the review candidate is provided with an in-depth understanding of the criteria by which he or she will be assessed and how to demonstrate these in the final professional review.